Investigating the Existence of Ribosomal Protein L5 Gene in Syrian Strain of Leishmania tropica Genome: Sequencing It and Evaluating Its Immune Response as DNA Vaccine - Mohammad Maarouf; Alyaa A. Abdlwahab (Journal of Parasitology Research)
Cutaneous leishmaniasis in Syria is caused mainly by Leishmania tropica. It represents a serious health problem, which has aggravated further after the civil war in the country. Until now, there are no effective protective strategies, safe therapy, or efficacious vaccine to protect from this infection. DNA vaccines represent a promising approach for achieving protection against leishmaniasis. The L5 ribosomal protein plays fundamental roles in the assembly process of the ribosome subunits, so this study has chosen the ribosomal protein L5 gene to design a DNA vaccine against Leishmania tropica infection. After proving the existence of the ribosomal protein L5 gene in a Syrian strain of Leishmania tropica (LCED Syrian 01), it was sequenced and cloned into a pCI plasmid, and the designed DNA vaccine was administered to BALB/c mice. The protective response was evaluated by measuring lesion development in immunized BALB/c mice for 6 weeks after challenging mice with the parasite. RT-qPCR was used to quantify IL-12, IFN-γ, and IL-4 in draining lymph nodes (DLNs) of immunized mice. In the final week, the parasite burden was determined in footpad lesions and local draining lymph nodes (DLNs). This study demonstrated the presence and expression of the ribosomal protein L5 gene in the Syrian strain of Leishmania tropica promastigotes. The sequence of the ribosomal protein cDNA L5 gene was determined and published in Genbank. The gene size was 918 bp. Expression was also demonstrated at the level of cDNA. This study also demonstrated that vaccination with the ribosomal protein L5 gene induces TH1 response in immunized mice. This response prevents the partial development of a skin lesion of Leishmania.